Securing Smart Sensing Production System using Deep Neural Network Model - V. Chandini, U. Mounika, V. Akshaya, K. Aarathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Internet of Things (IoT) enabled cyber physical systems such as Industrial equipment’s and operational IT to send and receive data over internet. This equipment’s will have sensors to sense equipment condition and report to centralized server using internet connection. Sometime some malicious users may attack or hack such sensors and then alter their data and this false data will be report to centralized server and false action will be taken. Due to false data many countries equipment and production system got failed and many algorithms was developed to detect attack, but all these algorithms suffer from data imbalance (one class my contains huge records (for example NORMAL records and other class like attack may contains few records which lead to imbalance problem and detection algorithms may failed to predict accurately). To deal with data imbalance, existing algorithms were using OVER and UNDER sampling which will generate new records for FEWER class only. To overcome from this issue, we are introducing novel technique without using any under or oversampling algorithms. The proposed technique consists of 2 parts which includes auto encoder and deep neural networks (DNNs).